Building Digital Adaptation Chains in Higher Education: From Digital Learning Readiness to Retention through Resilience and Competency Development - Yolanda Oktarina; Suharno Pawirosumarto; Zefriyenni Zefriyenni (Dinasti International Journal of Education Management and Social Science, 2026)
Digitised higher education increasingly relies on platform-based teaching, assessment, and reporting systems, yet this shift can intensify academic workload and create retention risks when lecturers face persistent digital frictions. This study develops and tests a mechanism-based digital adaptation chain to explain how Digital Learning Readiness (DLR) becomes workforce-sustainable in digitised higher education. Using survey data from 248 lecturers in private nursing higher education institutions and analysing the model with PLS-SEM, the study estimates a serial mediation process linking readiness to lecturer retention intention through academic resilience and competency development. The results support the proposed mechanism: DLR strengthens academic resilience, resilience enables competency development, and competency development emerges as the most proximal driver of retention intention. Notably, readiness alone is insufficient to sustain retention when it is not converted into adaptive capacity and enacted competence, consistent with a “readiness is not enough” interpretation. By shifting readiness research from adoption preparedness toward sustainability mechanisms, the study contributes a process explanation of workforce stability in digital education. The findings offer actionable guidance for institutions and policymakers to sequence interventions—engineering readiness, scaffolding resilience, and institutionalising competency development—to ensure that digital transformation remains people-sustainable.